(untitled) (Research, Society and Development, 2025)
Historically, the collective organization and struggle of workers has been an important factor in improving or maintaining the working environment and conditions. Although several struggles by digital platform workers, particularly app delivery riders, have been recorded in the last decade, few have resulted in lasting achievements. The objective of this article is to present a review study on the sources of power of app delivery riders, using the concepts of structural power and associative power. Finally, we address three cases in which the riders’ struggles also sought to affect the companies’ intangible assets: the Breque dos Apps in Brazil in 2020; the struggle in the Deliveroo IPO in the United Kingdom in 2021; and the struggle of eFood delivery workers in Greece also in 2021. The discussions are based mainly on a narrative literature review in English and Portuguese on forms of organization and struggles of app delivery riders in Brazil and around the world. The main conclusions are that app delivery riders have low structural power, with associative power still insufficient to significantly change working conditions and pay. In addition, striking the network effect of these companies has already proven to be possible and strategic to exert power over them.